Urban green space degradation: an experience of Kuala Lumpur city - Mohd Yusof, Mohd Johari; Shafri, Helmi; Abu Kasim, Junainah (Microthink Institute, 2019)
Recently, Kuala Lumpur (KL) urban green space essentially was converted to artificial surface due to the urbanization process. The scarcity land in the city besides government new initiatives on infrastructure and affordable housing scheme has put an extra demands and request for developments to enter green spaces zone throughout the city’s boundary. This study aimsto review the literature on green space issues in KL, as well as to explore the use of Geographical Information System (GIS) that could provide a comprehensive and reliability information of green space predominantly used by urban planners and decision makers. There is a need for Kuala Lumpur City Hall (DBKL) to map and monitor the gazetted green spaces changes aided by advance technology to ensure the city were plan well and developed in a sustainable way. The technology is extensively used for managing, controlling and mapping the urban green spaces changes and effectively use as an aided tool for planners in planning the green space developments effectively.